Pancreatic Carcinoma: Exploring its Relationship with Diabetes and the Potential Chemopreventive Effects of Metformin - Mahajan, Divya; Pandey, Awadesh kumar (Asian Pacific Journal of Cancer Biology, 2024)
Background: Pancreatic cancer and type 2 diabetes mellitus have been found to be interrelated, with emerging evidence suggesting that metformin may have a chemoprotective role in reducing the risk of pancreatic cancer in patients with diabetes. Methods: A comprehensive systematic search was conducted across databases, including PubMed, Web of Science, and the Cochrane Library. The search terms included "metformin," "biguanide," "pancreatic cancer," "pancreatic tumor," and "diabetes mellitus" in the title and abstract fields. Results: A meta-analysis of 18 studies using a random-effects model showed that metformin use was associated with a reduced risk of pancreatic cancer in patients with type 2 diabetes, compared to those who did not use metformin. Conclusion: This review highlights the chemoprotective effect of metformin in reducing the risk of pancreatic cancer among diabetic patients. Further research is needed to explore the mechanisms behind this association and to confirm these findings.